New approaches to measuring the comprehensiveness of primary care physicians. (6th January 2019) - O'Malley, Ann S.; Rich, Eugene C.; Shang, Lisa; Rose, Tyler; Ghosh, Arkadipta; Poznyak, Dmitriy; Peikes, Deborah
Abstract : Objective: To develop claims‐based measures of comprehensiveness of primary care physicians (PCPs) and summarize their associations with health care utilization and cost. Data Sources and Study Setting: A total of 5359 PCPs caring for over 1 million Medicare fee‐for‐service beneficiaries from 1404 practices. Study Design: We developed Medicare claims‐based measures of physician comprehensiveness ( involvement in patient conditions and new problem management ) and used a previously developed range of services measure. We analyzed the association of PCPs' comprehensiveness in 2013 with their beneficiaries' emergency department, hospitalizations rates, and ambulatory care‐sensitive condition (ACSC) admissions (each per 1000 beneficiaries per year), and Medicare expenditures (per beneficiary per month) in 2014, adjusting for beneficiary, physician, practice, and market characteristics, and clustering. Principal Findings: Each measure varied across PCPs and had low correlation with the other measures—as intended, they capture different aspects of comprehensiveness. For patients whose PCPs' comprehensiveness score was at the 75th vs 25th percentile (more vs less comprehensive), patients had lower service use ( P  < 0.05) in one or more measures: involvement with patient conditions : total Medicare expenditures, −$17.4 (−2.2 percent); hospitalizations, −5.5 (−1.9 percent); emergency department (ED) visits, −16.3 (−2.4 percent); new problem management : total Medicare expenditures, −$13.3 (−1.7 percent); hospitalizations, −7.0 (−2.4 percent); ED visits, −19.7 (−2.9 percent); range of services : ED visits, −17.1 (−2.5 percent). There were no significant associations between the comprehensiveness measures and ACSC admission rates. Conclusions: These measures demonstrate strong content and predictive validity and reliability. Medicare beneficiaries of PCPs providing more comprehensive care had lower hospitalization rates, ED visits, and total Medicare expenditures.